2021
DOI: 10.5194/acp-21-17953-2021
|View full text |Cite
|
Sign up to set email alerts
|

Diverse mixing states of amine-containing single particles in Nanjing, China

Abstract: Abstract. The mixing states of particulate amines with different chemical components are of great significance in studying the formation and evolution processes of amine-containing particles. In this work, the mixing states of single particles containing trimethylamine (TMA) and diethylamine (DEA) are investigated using a high-performance single-particle aerosol mass spectrometer located in Nanjing, China, in September 2019. TMA- and DEA-containing particles accounted for 22.8 % and 5.5 % of the total detected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…In particular, the influence of coal combustion associated with heating and industrial production is an important feature that distinguishes the difference of amine sources between the YRD and PRD areas and the northern areas. It should be pointed out that the above analysis identified the origins of potential contributors (i.e., gas‐phase amines) to the formation of particle‐phase amine salts, as suggested by many previous studies (Berta et al., 2023; Cheng et al., 2018; Liu et al., 2020; Zhong et al., 2021; Zhou et al., 2019). Recently, a study about the contributions of anthropogenic sources to amines in PM 2.5 suggested that the formation of particle‐phase amine salts (e.g., MA and DMA) was closely associated with the origins of gas‐phase amines (C. Liu et al., 2022).…”
Section: Resultssupporting
confidence: 60%
“…In particular, the influence of coal combustion associated with heating and industrial production is an important feature that distinguishes the difference of amine sources between the YRD and PRD areas and the northern areas. It should be pointed out that the above analysis identified the origins of potential contributors (i.e., gas‐phase amines) to the formation of particle‐phase amine salts, as suggested by many previous studies (Berta et al., 2023; Cheng et al., 2018; Liu et al., 2020; Zhong et al., 2021; Zhou et al., 2019). Recently, a study about the contributions of anthropogenic sources to amines in PM 2.5 suggested that the formation of particle‐phase amine salts (e.g., MA and DMA) was closely associated with the origins of gas‐phase amines (C. Liu et al., 2022).…”
Section: Resultssupporting
confidence: 60%
“…The number fraction of particles containing a specific ion in total particles was obtained through a conventional ion search procedure with COCO v1.4 software. The particle size detected by SPAMS was not scaled by a scanning mobility particle sizer for potential deviations caused by size-dependent particle transmission of the aerodynamic lens employed in SPAMS; nevertheless, it still captured the underlying trend of particle size evolution. ,, …”
Section: Methodsmentioning
confidence: 99%
“…This study investigates the importance of direct SO 2 reactions in sulfate aerosol formation in the absence of •OH radicals. Long-term measurements have continually revealed the presence of abundant ammonia and amines in ambient air, including in the marine environment [31,32], and their role has mainly been limited to stabilizing sulfate clusters. Herein, we have investigated sulfate formation from SO 2 oxidation assisted by MEA using density functional theory calculations and kinetic modeling.…”
Section: Introductionmentioning
confidence: 99%